Early cardiovascular autonomic dysfunction, b cell function andinsulin resistance in obese adolescents - Rabbone, I.; Bobbio, A.; Rabbia, F.; Bertello, et al., M. C. (Acta Biomedica Atenei Parmensis, 2009)
Aims: The aim of this study was to assess the metabolic and cardiovascular autonomic phenotype in adolescent obesity. Methods: Eighteen non diabetic obese individuals and ten lean age-matched control adolescents were included in the study. All subjects underwent Oral Glucose Tolerance Test (OGTT) with insulin and glucose determination for the calculation of AUC, OGIS, Quicki, and disposition index. Cardiovascular assessments included 24-hour Holter ECG for HRV measurements, ABP monitoring and echocardiography. Results: Obese adolescents had higher serum lipids, reduced insulin sensitivity and higher insulin resistance. Obese individuals showed indeed a normal beta-cell function, with insulin AUC and disposition index similar to controls. However, obese adolescents presented a progressive reduction of vagal indexes (RMSSD, HF) and an increase in sympathetic indexes (LF, LF/HF), which correlated with OGIS and beta-cell function parameters. Conclusion: Adolescent obesity is characterized by insulin resistance with normal beta-cell function. Metabolic modifications may lead to an early impairment of the autonomic pattern.